How important is variability in consumer credit limits? - Scott L. Fulford (Federal Reserve Bank of Boston, 2014)
Credit limit variability is a crucial aspect of the consumption, savings, and debt decisions of households in the United States. Using a large panel, this paper first demonstrates that individuals gain and lose access to credit frequently and often have their credit limits reduced unexpectedly. Credit limit volatility is larger than most estimates of income volatility and varies over the business cycle. While typical models of intertemporal consumption fix the credit limit, I introduce a model with variable credit limits. Variable credit limits create a reason for households to hold both high interest debts and low interest savings at the same time, since the savings act as insurance. Simulating the model using the estimates of credit limit volatility, I show that it explains all of the credit card puzzle: why around a third of households in the United States hold both debt and liquid savings at the same time. The approach also offers an important new channel through which financial system uncertainty affects household decisions.
Keywords: E21; D91; D14; 330; credit card puzzle; intertemporal consumption; precaution; credit limits; household finance